Real-Time Embedded Systems - Mihai T. Lazarescu (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Real-time and networked embedded systems are important bidirectional bridges between the physical and the information worlds. Embedded intelligence is increasingly pervading industry, infrastructure, and public and private spaces, being identified as an emerging societal and economic "neural system" that supports both societal changes and economic growth. As cost/performance improves, objects connected in everyday life increasingly rely on embedded intelligence in an ever-growing array of application fields, specialized technologies, and engineering disciplines. While this process gradually builds the IoT, it exposes a series of specific non-trivial timing and other extra-functional requirements and system properties that are less common in other computing areas. The ten articles in this book propose solutions to the specific open problems of cyber-physical and real-time embedded systems applicable to both traditional application domains, such as industrial automation and control, energy management, automotive, aerospace and defense systems, as well as emerging domains, such as medical devices, household appliances, mobile multimedia, gaming, and entertainment systems.]